TEACHER PROFESSIONAL DEVELOPMENT AND LEARNING OUTCOMES IN THE 21ST CENTURY - Sophie Barat Achieng, Dr. Madeleine (IJRDO- Journal of Educational Research, 2024)
Teacher professional development can be defined as those processes and activities designed to enhance the professional knowledge, skills and attitudes of teachers. Sophisticated forms of teaching are now needed to develop student competencies such as deep mastery of content, critical thinking, complex problem solving, effective communication and collaboration and self-efficacy. Effective professional development is needed to help teachers learn and refine instructional strategies required for these skills. This has become a top priority worldwide. Research has noted that many professional development initiatives appear ineffective in supporting changes in teachers’ practices and student learning. All rounded student development no longer refers to intellectual growth only but involves mastery of various skills such as critical thinking, problem solving, communication and collaboration. In order to effectively foster the development of 21st century skills in learners, teachers themselves must have at least a good command of skills and be well prepared in their own capacity to impart such skills to students. The current study therefore seeks to highlight the various skills and capacities that teachers need to maximize their potential in cultivating students’ 21st century skills. The findings of this study may help directors and managers of learning institutions address challenges of teacher professional development in order to improve the 21st century learning outcomes.